2015
DOI: 10.7575/aiac.ijalel.v.5n.2p.97
|View full text |Cite
|
Sign up to set email alerts
|

Are Emotionally Intelligent EFL Teachers More Satisfied Professionally?

Abstract: Despite the fact that Intelligence Quotient (IQ) is an important factor in one's success in terms of working environment, it is believed that emotional quotient or EQ plays a more important role. With that in mind, this study investigated the relationship between emotional intelligence and job satisfaction of English as Foreign Language (EFL) teachers who work at private language institutes in Iran/Shiraz. Furthermore, this study tried to answer whether there is a significant difference between emotional intel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
3
5
0
Order By: Relevance
“…The findings of the study are consistent with Ghanizadeh and Moafian (2010), and Vaezi and Fallah (2011) studies, where they found significant differences in teachers' EI across years of teaching experience. The result of the current study is in line with Hekmatzadeh, Khojasteh and Shokrpour (2016), where they reported significant differences in teachers' EI across gender.…”
Section: Discussionsupporting
confidence: 91%
“…The findings of the study are consistent with Ghanizadeh and Moafian (2010), and Vaezi and Fallah (2011) studies, where they found significant differences in teachers' EI across years of teaching experience. The result of the current study is in line with Hekmatzadeh, Khojasteh and Shokrpour (2016), where they reported significant differences in teachers' EI across gender.…”
Section: Discussionsupporting
confidence: 91%
“…The result of the current study is in line with Hekmatzadeh, Khojasteh and Shokrpour (2016), where they reported significant differences in teachers' EI across gender.…”
Section: Discussionsupporting
confidence: 81%
“…For example, Karavas (2010) found in her study conducted with Greek EFL teachers that the job satisfaction levels of male teachers were higher than those of women, which may be a sign about their life satisfaction levels as well. On the other hand, in their study, Hekmatzadeh, Khojasteh and Shokrpour (2016) found significant differences between the professional satisfaction levels of female and male teachers. According to the results of the present study, the reason why the life satisfaction levels of female teachers were found to be high might be that the teaching profession is preferred by women more, and teaching is suited to women more in society.…”
Section: Discussion Interpretations and Recommendationsmentioning
confidence: 78%